Kaunas Art School and “revolutionary artists” movement in Lithuania in 1930s - Žalkauskaitė, Gerda (Vilnius University Open Series, 2024)
The article examines the history of communist activities among students (Stepas Žukas, Boleslovas Motuza, Vytautas Mackevičius, Bronius Žekonis, Petras Vaivada, Irena Trečiokaitė, Liuda Vaineikytė) of the Kaunas Art School during the interwar period in independent Lithuania. It analyzes the academic conditions, artists connections with educators and fellow communist sympathizers, delves into their backgrounds, family social and material situations, and other factors that could have influenced their radicalization and involvement in the Communist Party of Lithuania.